R&D Dynamics and Its Impact on Productivity and Export Demand in Swedish Manufacturing - Van Anh Vuong; Florin Maican; Matilda Orth; Mark Roberts (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In this paper we develop a structural empirical model that allows us to estimate the impact of R&D on firm profitability through two channels. In the first channel, R&D investment by the firm can impact the firm's production efficiency and lower its marginal cost. This productivity channel raises the firm's sales and profits in both the domestic and export market. The second channel is specific to exporting firms where R&D acts to increase the demand for the firm's products in foreign markets. Using micro data for Swedish manufacturing firms from 2000-2010 we estimate the impact of R&D investment on the unobserved component of the firm's productivity and export market demand. Our empirical results show that firm R&D investment has a statistically significant, positive effect on both the future productivity and the future export demand of the firm. For high-tech industries, we find that the impact of R&D investments on the demand shocks is twice as large as its impact on productivity. On the other hand, the impact of R&D investments on productivity in the low-tech industries is higher than on demand shocks.
Keywords: D22; F10; L60; 330